Health-OS: A Position Paper - Kirovski, Darko; Oliver, Nuria; Sinclair, Mike; Tan, Desney (Poster at the 1st International Workshop on Systems and Networking Support for Healthcare and Assisted Living Environments (HealthNet07), 2016)
The area of medical monitoring and diagnostics is of particular importance and relevance today. Modern nanotechnology has reduced prices and size of increasingly sophisticated sensors. Short-range wireless communication has become advanced enough to support inexpensive active sensor systems. Wearable computing devices are ubiquitous and increasingly powerful. As a result of these advances, a growing number of health monitoring systems with increasingly sophisticated capabilities are available today. Moreover, there is growing public interest in products that allow individuals (from children to elders) to monitor and improve their own health. These trends create an increasing demand for platforms that aim to support and improve one’s health and lifestyle. We propose Health-OS, a middleware platform for multidevice sensing that transparently monitors, stores, transmits, analyzes and presents various physiologically based signals. The objective is to unify an open group of sensing mechanisms with a myriad of computing platforms and applications via a common platform equipped with a software development kit.